Hire and keep the best people : 21 practical and proven techniques you can use immediately - Tracy, Brian (Berrett-Koehler Publishers, 2001)
The biggest requirement for success in any business is the ability to attract and retain excellent employees, yet most managers have never ever received any formal training in the process of personnel selection. And, if you're like most managers, you probably don't have time for a course on the subject anyway, because your needs for personnel know-how are pressing and immediate. Hire and Keep the Best People details 21 of the most important, proven principles of employee recruitment and retention. It's a quick read that tells you everything you need to know to attract the most capable, committee.